2008
DOI: 10.1590/s1982-56762008000500002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative epidemiology of citrus tristeza in Cuba and citrus sudden death in Brazil

Abstract: Citrus Sudden Death (CSD) is a disease of unknown etiology, reported only in Brazil. Due to similarities between the epidemiology of CSD in Brazil and Citrus Tristeza (CT) in other countries, this work aimed to compare CSD and CT in Cuba. Besides testing the hypothesis of shared epidemiological patterns, the data generated can be used to carry out control strategies if CSD breaks out in Cuba. Seven epidemic data sets were statistically compared for each disease by analyzing their progress in time and the depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Studies have suggested an aggregated spatial structure of symptomatic plants with CSD (Bassanezi et al, 2003;Bassanezi and Laranjeira, 2007), and shown that the CSD annual rate increases during periods under study (Bassanezi et al, 2003;Batista et al, 2008). The present work shows strong evidence of temporal clustering for CSD, which is mainly characterized by temporal clustering in the beginning of the trial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested an aggregated spatial structure of symptomatic plants with CSD (Bassanezi et al, 2003;Bassanezi and Laranjeira, 2007), and shown that the CSD annual rate increases during periods under study (Bassanezi et al, 2003;Batista et al, 2008). The present work shows strong evidence of temporal clustering for CSD, which is mainly characterized by temporal clustering in the beginning of the trial.…”
Section: Resultsmentioning
confidence: 99%
“…In the current level of knowledge, these tests have not been used for temporal analysis of agricultural diseases. The majority of the temporal, specifically for CSD, are used for analyzing the disease behavior progression over time by estimating monthly rates (Batista et al, 2008) or by using spatial and temporal analyses (Bassanezi et al, 2005), models of cellular automata (Peixoto et al, 2008) and, autologistic models (Krainskiet al, 2008), rather than testing against the CTR hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…The apparent relationship between quadrat size and both the slope and intercept of the BPL regression has also been noted in previous field studies (e.g. Bassanezi et al ., ; Dallot et al ., ; Humeau et al ., ; Batista et al ., ). Although these results are clear, field studies that provide a basis for characterizing observed patterns of disease do not necessarily elucidate the process(es) underlying those patterns.…”
Section: Discussionmentioning
confidence: 97%